Пимекролимус в лечении атопического дерматита у детей. Вопросы безопасности и эффективности. Опыт пятилетнего применения - D. V. Zaslavsky (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
A growth in the incidence rate for atopic dermatitis (AD) in infants has been observed for this decade. Early formation of AD (at the age of 3-6 months) is observed in 45% of infants, and in 60% of infants - during the first year of life. As many as 65% of children (by the age of 7) and 74% of children (by the age of 16) suffering from AD have a spontaneous remission of the disease. As many as 20-43% of children suffering from AD further develop bronchial asthma, and the incidence rate of allergic rhinitis is twice as high. In spite of the fact that topical corticosteroids (TCS) are prescribed frequently enough, there is a need in the non-hormonal therapy due to poor compliance with the TCS treatment regimen in connection with side effects. Treatment of AD is often complicated by the colonization with Staphylococcus aureus and inefficacy of the external therapy with topical corticosteroids because many patients with AD have a high level of IgE against the superantigen of Staphylococcus. 1% pimecrolimus cream (PIM) and TCS were compared in a long-term large-scale study involving younger children suffering from mild to moderate AD. Materials and methods. The five-year open-label study involved 2,418 children, who were randomized into groups receiving PIM (n = 1205; in case of an aggravation - short-term administration of TCS) or TCS (n = 1213). The main goal of the study was to compare the safety of these two methods of treatment; an auxiliary goal was to confirm the long-term efficacy of PIM. Treatment was considered to be successful if the score based on the IGA scale was 0 (clean skin) or 1 (almost clean). Results. The effect in both groups of the drugs - PIM and TCS - was fast, and the success of treatment was recorded for >50% of patients by Week 3. In both groups, treatment was determined to be successful after 5 years in >85% of patients, and treatment of manifestations of AD on the face was efficient in 95% of all subjects. In the PIM group, the need in steroids was considerably lower than in the TCS group (7 days of administration vs. 178 days in the TCS group). In both groups, there were adverse events similar by their nature and frequency, and no disorders of humoral or cellular immunity were revealed. Conclusions. The long-term administration of PIM in case of mild to moderate AD in children was revealed to be safe and had no effect on the immune system. When PIM was used, the need in corticosteroids was considerably reduced (steroid-preserving effect). These data confirm that PIM is as efficient as TCS and can be used as the first-line therapy for mild to moderate AD in infants and younger children.